Effects of the thermal and magnetic paths on first order martensite transition of disordered Ni45Mn44Sn9In2 Heusler alloy exhibiting a giant magnetocaloric effect and magnetoresistance near room temperature. (18th April 2018) - Chabri, T; Ghosh, A; Nair, Sunil; Awasthi, A M; Venimadhav, A; Nath, T K
Abstract: The existence of a first order martensite transition in off-stoichiometric Ni45 Mn44 Sn9 In2 ferromagnetic shape memory Heusler alloy has been clearly observed by thermal, magnetic, and magneto-transport measurements. Field and thermal path dependence of the change in large magnetic entropy and negative magnetoresistance are observed, which originate due to the sharp change in magnetization driven by metamagnetic transition from the weakly magnetic martensite phase to the ferromagnetic austenite phase in the vicinity of the martensite transition. The noticeable shift in the martensite transition with the application of a magnetic field is the most significant feature of the present study. This shift is due to the interplay of the austenite and martensite phase fraction in the alloy. The different aspects of the first order martensite transition, e.g. broadening of the martensite transition and the field induced arrest of the austenite phase are mainly related to the dynamics of coexisting phases in the vicinity of the martensite transition. The alloy also shows a second order ferromagnetic → paramagnetic transition near the Curie temperature of the austenite phase. A noticeably large change in magnetic entropy (Δ S M = 24 J kg −1 K −1 at 298 K) and magnetoresistance (= −33% at 295 K) has been observed for the change in 5 and 8 T magnetic fields, respectively. The change in adiabatic temperature for the change in a magnetic field of 5 T is found to be −3.8 K at 299 K. The low cost of the ingredients and the large change in magnetic entropy very near to the room temperature makes Ni45 Mn44 Sn9 In2 alloy a promising magnetic refrigerant for real technological application.